APPLICATION OF AHP TO DETERMINE CRITICAL SUCCESS FACTOR FOR OUTSOURCING AUDIO PROJECT BASED SERVICE: A CASE STUDY OF PT. SHEFAI INDONESIA - Muhammad Faishal; Dina Dellyana (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This Research provides business process model for an organization that attempts to improve outsourcing strategy in the audio services sector. This research uses the case study approach by applying the Analytical Hierarchy Process (AHP) as a means to define critical success factors in outsourcing project-based audio services at PT. Shefai Indonesia. The research identifies the following as the seven most important criteria that are likely to determine the success of outsourcing: Adequate Communication Channels, Effective Feedback, Skilled Engineers, Skilled Voice Actor Pool, Skilled Project Manager, Turnaround Time Delivery, and Information Security. The study further combines internal (SWOT) and external (PESTEL) analyses to design a complete outsourcing workflow and business structure. To solve the problem, the business process incorporates five key stages, which are supported with CSFs at at critical points to enhance efficiency, vendor collaboration, and service quality